Modular assembly of plasmonic core–satellite structures as highly brilliant SERS-encoded nanoparticles. Issue 1 (8th November 2018) - Pazos-Perez, Nicolas; Fitzgerald, Jamie M.; Giannini, Vincenzo; Guerrini, Luca; Alvarez-Puebla, Ramon A.
Abstract : Herein, we present a fabrication approach that produces homogeneous core–satellite SERS encoded particles with minimal interparticle gaps (<2–3 nm) and maximum particle loading, while positioning the encoding agents at the gaps. Abstract : Herein, we present a fabrication approach that produces homogeneous core–satellite SERS encoded particles with minimal interparticle gaps (<2–3 nm) and maximum particle loading, while positioning the encoding agents at the gaps. Integration of plasmonic building blocks of different sizes, shapes, compositions, surface chemistries or encoding agents is achieved in a modular fashion with minimal modification of the general synthetic protocol. These materials present an outstanding optical performance with homogeneous enhancement factors over 4 orders of magnitude as compared with classical SERS encoded particles, which allows their use as single particle labels.